Early Brāhmī records in India (c. 300 B.C.-c. 300 A.D.); an analytical study: social, economic, religious, and administrative - Chakraborti, Haripada, 1912- (Sanskrit Pustak Bhandar, 1974)
A study of the sources of ancient Indian history.